Effectiveness of the extended parallel process model in promoting colorectal cancer screening. Issue 10 (20th July 2015) - Birmingham, Wendy C.; Hung, Man; Boonyasiriwat, Watcharaporn; Kohlmann, Wendy; Walters, Scott T.; Burt, Randall W.; Stroup, Antoinette M.; Edwards, Sandie L.; Schwartz, Marc D.; Lowery, Jan T.; Hill, Deirdre A.; Wiggins, Charles L.; et al.
Abstract Objective Relatives of colorectal cancer (CRC) patients are at increased risk for the disease, yet screening rates still remain low. Guided by the Extended Parallel Process Model, we examined the impact of a personalized, remote risk communication intervention on behavioral intention and colonoscopy uptake in relatives of CRC patients, assessing the original additive model and an alternative model in which each theoretical construct contributes uniquely. Methods We collected intention‐to‐screen and medical record‐verified colonoscopy information on 218 individuals who received the personalized intervention. Results Structural equation modeling showed poor main model fit (root mean square error of approximation (RMSEA) = 0.109; standardized root mean residual (SRMR) = 0.134; comparative fit index (CFI) = 0.797; Akaike information criterion (AIC) = 11, 601; Bayesian information criterion (BIC) = 11, 884). However, the alternative model (RMSEA = 0.070; SRMR = 0.105; CFI = 0.918; AIC = 11, 186; BIC = 11, 498) showed good fit. Cancer susceptibility (B = 0.319, p < 0.001) and colonoscopy self‐efficacy (B = 0.364, p < 0.001) perceptions predicted intention to screen, which was significantly associated with colonoscopy uptake (B = 0.539, p < 0.001). Conclusions Our findings provide support of the utility of Extended Parallel Process Model for designing effective interventions to motivate CRC screening in persons at increased risk when individual elements of the model are considered. Copyright © 2015 John Wiley & Sons, Ltd.